Internal Branding Processes in a Fashion Organization: Turning Employees into Brand Ambassadors - Murillo, Enrique; Sádaba, Teresa; Mir-Bernal, Pedro; Terán-Bustamante, Antonia; López-Sánchez, Oziel (Mercados y Negocios, 2024)
This research aims to empirically examine the internal branding processes implemented by a global sports fashion firm to turn all employees into competent brand ambassadors. Brand-oriented training was hypothesized as an antecedent of salesperson brand identification and brand commitment, which drive brand-aligned behavior, the critical trait of employee brand ambassadors. These hypotheses were tested by surveying 141 corporate and retail employees of a global sportswear fashion brand's regional operations in Mexico. The principal conclusion is that brand-oriented training proves a significant driver of salesperson brand identification. Furthermore, brand identification drives brand commitment and brand-aligned behavior among all company employees, not just salespersons.